CASE REPORT MALIGNANT GLOMUS TUMOR: A RARE CASE - Pamelia Mayorita; Mustika Sari; Zulda Musyarifah; Hera Novianti; Yessy Setiawati; Meta Zulyati Oktora (Yayasan Nusantara Hasana Berdikari, 2025)
Background: Glomus tumor is a rare mesenchymal neoplasm that accounts for less than 2% of all soft tissue tumors and 1.5% of extremity neoplasms. Malignant glomus tumors are exceptionally rare, comprising only 1-2.9% of all glomus tumors, and are often associated with significant diagnostic and therapeutic challenges. Case Presentation: We report a case of a 62-year-old male presenting with a painful lump on his left thumb, progressively enlarging over six months. Clinical examination revealed a 3x2x1 cm subungual mass with positive cold sensitivity and pin love tests. The patient underwent amputation, and histopathological analysis showed a proliferation of round-to-oval and spindle cells with nuclear atypia, frequent mitotic figures (>5/50 HPF), and atypical mitoses, consistent with malignant glomus tumor grade 2. Surgical margins and bone were free of tumor infiltration. Conclusion: This case highlights the importance of clinical-pathological correlation in diagnosing malignant glomus tumors, which remain a diagnostic challenge due to their rarity. Complete surgical excision with negative margins remains the gold standard for treatment, ensuring favorable outcomes and minimizing recurrence risk.